EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPETEAMS GAMES TOURNAMENT (TGT) TERHADAP KEMAMPUAN BERPIKIR LOGIS MATEMATIKA SISWA SMK - Tukmaida Simatupang; Marzuki Ahmad; Eva Yanti Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to describe the effectiveness of applying kooperatif tipe teams games tournament learning on students’ mathematical logical thinking ability on the topic linear equation system of two variables at the tenth grade students of SMKS Yayasan Pendidikan Islam Padang Lawas. This research was conducted by applying experimental method (one group pretest posttest design). Sample of this research is 30 students which taken by using cluster random sampling technique from 55 students. Observation and test were used in collecting the data. Observation sheet shows the average of applying kooperatif tipe teams games tournament learning is 4 (very good category). The result of the test shows average of students’ mathematical logical thinking ability before applying kooperatif tipe teams games tournament learning is 58 (enough category) and after applying kooperatif tipe teams games tournament learning is 85,85 (very good category). Furthermore by using pair sample ttest (SPSS 16) and N-Gain shows the significant value is less than 0.05 (0.000 <0.05). It’s concluded kooperatif tipe teams games tournament learning has the effect on students’ mathematical logical thinking ability on the topic linear equation system of two variables at the tenth grade students of SMKS Yayasan Pendidikan Islam Padang Lawas.